Significance of HbA1c test is a stable indicator of triglycerides in diagnosis and prognosis of diabetic patients - Rani, J. Sudha (International Journal of Research in Medical Sciences, 2020)
Background: The main purpose of the study was to highlight the relationship between glycosylated hemoglobin (HbA1c) and triglyceride levels in type 2 DM. Insulin resistance is associated with the elevated triglycerides (TG), and persons with type-2 diabetes are insulin resistant However, it is unknown what level of glycemia that causes an increase in TGL. Hence Therefore I am interested to determine the quantitative relationship between the hemoglobin A1C (HbA1c) and TGL. Methods: This descriptive study was conducted at GVPIHC&MT Marikavalasa, Visakhapatnam-4. The study population included 100 patients (not discriminate Male/ Female) of type 2 DM not on lipid lowering medication and 100 subjects without DM as controls from the department of General Medicine. For statistical analysis, Chi-square and Pearson’s correlation coefficient was used to find the association between triglyceride and HbA1c. Results: The association of high triglyceride was evaluated in type 2 DM group of HbA1c, with a cut-off value 7% patients had high triglycerides and showed a significant association with high HbA1c levels at p<0.0001. Conclusions: It has been shown from this study Triacylglycerol level are high with HbA1c (with a cut-off value 7%) level was found higher in diabetic patients when compared with the controls. Therefore, proper glycemic control should be maintained by maintaining HbA1c level less than 6.0% to prevent multifactorial disorder of diabetic complications.